Coordenação local do Eu(III) em híbridos orgânicos/inorgânicos emissores de luz branca - Carlos, Luís D.; Ferreira, Rute A. Sá; Zéa Bermudez, Verónica de; Bueno, Luciano A. [UNESP]; Molina, Celso [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Sociedade Brasileira de Química, 2001)
Eu3+ luminescence and EXAFS (Extended X-ray Absorption Fine Structure) results are presented for organic-inorganic hybrid gel hosts composed of a siliceous network to which small chains of oxyethylene units are covalently grafted by means of urea bridges. Coordination numbers for Eu3+ ions range from 12.8 to 9.7 with increasing Eu3+ concentration while the Eu3+-first neighbours mean distance is found to be constant at 2.48-2.49 Å in the same concentration range. Emission spectra display a broad band in the green/blue spectral region superposed to narrow lines appearing in the yellow/red region in such a way that for the eyes emission appears white. The broad band is assigned to intrinsic NH groups emission and also to electron-hole recombination in the nanosised siliceous domains. The narrow lines are assigned to intra-4f6, 5D0->7F0-4 Eu3+ transitions and from the energy position of the 7F0-4 levels a mean distance could be calculated for the Eu3+-first neighbours. The calculated results are in good agreement with the experimental ones obtained from EXAFS analysis.
Eu(III) local coordination in white light emitters organic-inorganic hybrids
Keywords: organic-inorganic hybrids; luminescence; EXAFS